Sperm quality impairment in males of couples with pregnancy loss is correlated with sexual dysfunction: a cross-sectional study - Xiaowei Yu; Songling Zhang; Xiao Yuan Zhang; Qun Wang (BMC, 2023)
Abstract Background Erectile dysfunction is a common problem in males of couples experiencing pregnancy loss. Erectile dysfunction in males with couple infertile has been extensively investigated and found to be closely linked with semen quality impairment and psychological distress, but it is less clear if this relation exists in males of couples experiencing pregnancy loss. Method A cross-sectional analysis of 437 men who attended our outpatient clinic between June 2021 and October 2021 for couple pregnancy loss. All subjects underwent a complete physical examination, palpation, inspection of the male genitalia, and semen analysis. Validated assessment tools for erectile dysfunction (the International Index of Sexual Function5 -IIEF-5) and anxiety (the seven-item Generalized Anxiety Disorder Scale- GAD-7) were used. Results Among 437 men of couples with pregnancy loss, we found several relevant sperm parameters confirmed a significant correlation between IIEF-5 scores and sperm parameters, including: sperm progressive motility (r = 0.1627, p = 0.001), sperm normal morphology (r = 0.1373, p = 0.004) and sperm DNA fragmentation (r =-0.1248, p = 0.009). Males with an IIEF-5 scores range between 5-11 presented the worst results in terms of sperm progressive motility (p = 0.002), normal morphology (p = 0.001), and SDF levels (p = 0.003). GAD-7 score, as well as anxiety level, was significantly higher in those males with an IIEF-5 score between 5 and 11 (p = 0.000). Conclusion Although current evidence does not demonstrate the importance of spermatozoa in the etiology of pregnancy loss, significant correlations have been observed between impaired sperm quality and low IIEF-5 scores. Also, anxiety is more likely to occur in males with sexual dysfunction.